2012
DOI: 10.2298/aci1201105r
|View full text |Cite
|
Sign up to set email alerts
|

Multiple port-site metastasis of incidental gallbladder carcinoma after laparoscopic cholecystectomy

Abstract: Laparoscopic cholecystectomy is a surgical procedure of choice for benign gallbladder diseases. In about 1-2% of cases histopathological examination demonstrate incidental gallbladder cancer (GBCA). We report a case of a 61 year old woman who developed port site metastases after laparoscopic cholecystectomy for adenocarcinoma of the gallbladder. Metastases appeared on all four port sites. Review of literature regarding incidental GBCA an port site metastases was also performed. We conclude that the retrieval b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…[14] Razontovic et al, reported a 61-yearold female who presented with PSM post-surgery and died after 2 months. [15] Conversely, Sandor et al, presented a case of PSM of GBC that was treated and followed up 11 months postsurgery with no further complaints. [16] Ninety percent of PSM cases were found in the trocar site, from where the gallbladder specimen was extracted.…”
Section: Discussionmentioning
confidence: 99%
“…[14] Razontovic et al, reported a 61-yearold female who presented with PSM post-surgery and died after 2 months. [15] Conversely, Sandor et al, presented a case of PSM of GBC that was treated and followed up 11 months postsurgery with no further complaints. [16] Ninety percent of PSM cases were found in the trocar site, from where the gallbladder specimen was extracted.…”
Section: Discussionmentioning
confidence: 99%
“…Occult GBC is seen on postoperative histopathology in up to 3% of cases undergoing cholecystectomy for benign diseases. [ 3 ] Laparoscopic handling of GBC is associated with the development of PSM, seen in up to 29% of cases. [ 1 , 2 ] Some authors also suggested port-site resection to decrease the development of PSM in incidental GBCs detected postlaparoscopic cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the number of laparoscopic surgical procedures has led to the discovery of an increased number of incidental gallbladder carcinomas at an early stage [2]. Histopathological examination reveals an incidental carcinoma in approximately 1-2% of patients undergoing laparoscopic cholecystectomy [3][4][5].…”
Section: Introductionmentioning
confidence: 99%